ANALISIS SEKTOR BASIS DAN SEKTOR NON BASIS TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI MALUKU (STUDI KASUS KABUPATEN KOTA) - Ali Tutupoho (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2019)
The purpose of this study was to analyze the influence of the base sector and non-base sectors on economic growth in Maluku Province in 2011-2017. The analytical method used the data panel regression analysis model, and to determine the significance level of each regression coefficient of the independent variable on the dependent variable, the statistical test is used. This study also uses Dynamic Location Quotient (DLQ) analysis. The analysis shows that each region tends to show differences in the potential of its economic sectors. Because of the different contributions of each economic sector in different regions, the sectors that are superior in a region are relatively different from other regions. The results of the analysis also show that the base sector variable and the non-base sector have a significant positive effect on economic growth in the Regency / City of Maluku Province.